USE OF NEW PEDAGOGICAL TECHNOLOGIES IN TEACHING THE SUBJECTS OF INDUSTRIAL SANITATION AND LABOR HYGIENE (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
In this article, the possibilities of using new pedagogical technologies in the course of the lesson are highlighted on the example of topics of industrial sanitation and occupational hygiene. With the help of basic words and expressions related to science, the content and essence of the subject of science is revealed using "Cubic strategy", "Sinquevin", "Venn diagram" and "Cluster" as well as new pedagogical methods.